Conservation of fungal and animal nicotinamide adenine dinucleotide phosphate oxidase complexes. Issue 6 (23rd February 2015) - Scott, Barry
Summary Nicotinamide adenine dinucleotide phosphate (NADPH) oxidases (Nox) are a group of eukaryotic flavoenzymes that catalyse the reduction of dioxygen to the superoxide anion using electrons provided by NADPH. An integral membrane flavocytochrome b558 heterodimer, composed of the catalytic subunit gp91phox and the adaptor protein p22phox, is essential for catalytic activity of the mammalian Nox2 complex. Two homologues of the mammalian gp91phox, NoxA and NoxB, have been identified in fungi and shown to be crucial for distinct fungal cell differentiation and developmental processes, but to date, no homologue of the p22phox adaptor protein has been identified. Isolation of a mutant from Podospora anserina with a phenotype identical to a previously characterised PaNox1 mutant, combined with phylogenetic analysis, identified a fungal homologue of p22phox called PaNoxD. The same adaptor protein was shown to be a component of the Botrytis cinerea NoxA complex as supported by the identical phenotypes of the bcnoxA and bcnoxD mutants and direct physical interaction between BcNoxA and BcNoxD. These results suggest that NoxA/NoxD is the fungal equivalent of the mammalian gp91phox/p22phox flavocytochrome complex. Tetraspanin (Pls1) mutants of P. anserina and B. cinerea have identical phenotypes to noxB mutants, suggesting that Pls1 is the corresponding integral membrane adaptor for assembly of the NoxB complex.